Kontribusi Kementerian Agama dan Pemerintah Daerah Kabupaten Lima Puluh Kota dalam Penguatan Lembaga Pendidikan Qur’an dan Diniyah - Ifkar, Ifkar (UIR Press, 2025)
Qur'anic and Diniyah Education Institutions in Kabupaten Lima Puluh Kota have a strategic position in providing access to Qur'anic education services and early Islamic religious education for children. Most of these institutions face the limitations of inadequate education standards. Therefore, serious attention from relevant parties is needed so that the role of these institutions can be optimized. This research aims to analyze the contribution of the Ministry of Religious Affairs and the Regional Government of Lima Puluh Kota in strengthening Qur'anic and Diniyah Education Institutions. The research method used is qualitative with data collection techniques through interviews and documentation. Respondents included teachers, heads of TPQ and MDTA, as well as administrators of FKDT, BKSTPQ, the Head of the Ministry of Religious Affairs Office, the Head of the Education Office, and the Head of the Welfare Section. The results showed three main contributions, namely: (1) legality strengthening through the presence of Law No. 18/2019 on Pesantren which is the legal basis for the recognition, empowerment, and facilitation of pesantren in the national education system, (2) institutional strengthening through the issuance of Regent Regulation No. 33/2022 on Guidelines for the Development of Tahfizh Houses and Tahfizh Programs and the preparation of the Draft Regional Regulation on Pesantren, strengthened by technical implementation, and (3) financial strengthening through special allocations in the APBD for teacher welfare and capacity building.